Analisis Digital Marketing Penjualan Baju Brand Matahari Di ICH Danareja - Purwanto, Inaaratul Chusna Ichda (Universitas katolik Musi Charitas, 2019)
ICH Danareja describes home industry players engaged in the sale of clothing brand. The implementation of the sale of clothing matahari brand of ICH Danareja tried was with an store system offline and online marketing through social media. The case experienced by ICH at this time was the least method of selling clothing matahari brand through promotional media facilities. The average sales in 2018 per month are only around 300 pcs of clothing produced from conventional and online marketing with a total income of IDR. 15,000,000/month. This situation is quite low because it is fitting for the sales target of 500 pcs of clothing and has not targeted the use of facilities digital marketing as well as indicating depreciation in sales volume by 40% in 2016, 45% in 2017 and 50% in 2018. Research on the problems studied clothing sales can be improved in the manner of the Boston Consulting Group. The result of the level of clothing sales volume of the matahari brand an attractive energy development market of 0, 03%, the total development of the market share is 0, 6%, the level of development of product sales reaches 504 pcs per month. So that it can fulfill the sales target of 500 pcs of clothes per month. Next, analyzing benchmarking that refers to the strategy canvas, the price advantage of ICH is relatively standard and affordable, the lowest price of IDR. 35,000. Keywords: Boston Consulting Group, Benchmarking, Digital Marketing